Paracetamol for the treatment of patent ductus arteriosus in preterm neonates: a systematic review and meta-analysis. Issue 2 (17th August 2015) - Terrin, Gianluca; Conte, Francesca; Oncel, Mehmet Yekta; Scipione, Antonella; McNamara, Patrick J; Simons, Sinno; Sinha, Rahul; Erdeve, Omer; Tekgunduz, Kadir S; Dogan, Mustafa; Kessel, Irena; Hammerman, Cathy; et al.
Abstract : Objectives: We performed a systematic review and meta-analysis of all the available evidence to assess the efficacy and safety of paracetamol for the treatment of patent ductus arteriosus (PDA) in neonates, and to explore the effects of clinical variables on the risk of closure. Data source: MEDLINE, Scopus and ISI Web of Knowledge databases, using the following medical subject headings and terms: paracetamol, acetaminophen and patent ductus arteriosus. Electronic and manual screening of conference abstracts from international meetings of relevant organisations. Manual search of the reference lists of all eligible articles. Study selection: Studies comparing paracetamol versus ibuprofen, indomethacin, placebo or no intervention for the treatment of PDA. Data extraction: Data regarding efficacy and safety were collected and analysed. Results: Sixteen studies were included: 2 randomised controlled trials (RCTs) and 14 uncontrolled studies. Quality of selected studies is poor. A meta-analysis of RCTs does not demonstrate any difference in the risk of ductal closure (Mantel–Haenszel model, RR 1.07, 95% CI 0.87 to 1.33 and RR 1.03, 95% CI 0.92 to 1.16, after 3 and 6 days of treatment, respectively). Proportion meta-analysis of uncontrolled studies demonstrates a pooled ductal closure rate of 49% (95% CI 29% to 69%) and 76% (95% CI 61% to 88%) after 3 and 6 days of treatment with paracetamol, respectively. Safety profiles of paracetamol and ibuprofen are similar. Conclusions: Efficacy and safety of paracetamol appear to be comparable with those of ibuprofen. These results should be interpreted with caution, taking into account the non-optimal quality of the studies analysed and the limited number of neonates treated with paracetamol so far.